The Influence of Environmental, Social, and Governance (ESG) Disclosure on Firm Financial Performance - Raisa Almeyda; Asep Darmansya (Institut Teknologi Sepuluh Nopember, 2019)
The aim of this study is to do research about non-financial aspect that has influence toward the companies’ financial performance, that will highlight the scores of companies’ ESG (Environment, Social, Governance) disclosure. Nowadays, investors take into account the non-financial aspect into their investment decision, such as ESG performance as a risk measurement. The mixed of results found in the previous studies regarding the correlation between company ESG/CSR and financial performance warranted us to conduct more research in this particular topic. We conducted research on companies in the real estate sector since its long-term nature of investment is aligned with long-term ESG goals. The samples of companies were collected from seven countries with the strongest economy worldwide, the G7. The financial performance is measured by both in the perspectives of accounting and stock market, which are ROA, ROC, Stock Price, and P/E. The panel data was collected over five years (2014-2018), using STATA to run multivariate regressions to test for the correlations. The results indicate that there is a statistically significant positive relationship between the ESG disclosure with firm’s ROA and ROC, but no significant relationship with Stock Price and P/E. Furthermore, we found that there is a statistically significant positive relationship between the Environmental factor towards the firm’s ROC and Stock Price. Lastly, the study also reveals that there’s no significant relationship between the Social factor and Governance factor with firm financial performance. The results show that a high transparency regarding ESG information could improve the financial performance. Thus, it is advisable for investors, company management, decision-makers, and industry regulators to consider the importance of the ESG disclosure